The influence of physical exercise on adolescents’ negative emotions: the chain mediating role of academic stress and sleep quality - Yile Liu; Yijuan Lu; Hongjiang Wang; Enming Tian; Xiang Su; Senjie Su; Wu Zhou; Yue Gao (BMC Pediatrics)
Abstract Introduction Physical exercise is related to negative emotions in adolescents. However, the specific processes by which academic stress mediates the relationship between physical exercise and negative emotions remain uncertain. This study aims to explore the relationship between physical exercise and negative emotions in adolescents and its underlying mechanisms, and to construct a comprehensive model that links these variables. Methods The data were derived from the 2020 China Family Panel Studies (CFPS). The Physical Activity Rating Scale-3 (PARS-3) and the Center for Epidemiologic Studies Depression Scale − 20 (CES-D-20) were used to measure the level of physical exercise and negative emotions respectively. We used a questionnaire survey to evaluate how academic stress and sleep quality act as mediators in the relationship between physical exercise and negative emotions. Results Physical exercise was negatively correlated with negative emotions, with a stronger direct effect observed in males compared to females. The mediating effect of sleep quality accounted for 53.03% of the total effect, the mediating effect of academic stress accounted for 40.33% of the total effect, and the chained mediating effect of academic stress and sleep quality accounted for 3.87% of the total effect. Conclusion There is a significant relationship between physical exercise and the generation of negative emotions. academic stress and sleep quality play a chain mediating role in this connection. Educators and parents can encourage adolescents to actively participate in physical exercise, appropriately reduce academic stress, and improve sleep quality to prevent negative emotions.